Phaleria macrocarpa (Boerl.) Scheff Fruit: A Potential Source of Natural Antioxidant - Hendra, Rudi; Haryani, Yuli (Pharmacology and Clinical Pharmacy Research)
Phaleria macrocarpa (Scheff.) Boerl is originated from Papua Island, Indonesia. There have been only limited attempts to explore the biological properties of this plant in relation to their medicinal use. This study aimed to examine antioxidant activity of P. macrocarpa fruit. Extraction of pericarp and mesocarp of P. macrocarpa were performed using soxhlet method with ethyl acetate as the solvent. Antioxidant activity was characterized in various in vitro model systems, including DPPH and ferric reducing antioxidant assay. We found that the highest amount of phenolic compounds and flavonoids were found in the pericarp (58.3±0.07 mg/g DW and 127.8±1.08 mg/g DW, respectively). The results showed that pericarp had higher antioxidant activity (IC50= 122.4±1.14 µg/ml) compared to mesocarp (IC50=175.48 ±1.75 µg/ml). In conclusion, the result of this study indicated the possible application of P. macrocarpa as a source of natural antioxidant compound.Keywords: antioxidant, Phaleria macrocarpa, phenolic compounds, flavonoids